Magnesium Orotate Influence on Thoracic Aorta in Laboratory Rabbits Receiving Levofloxacin - N. V. Izmozherova; D. V. Zaytsev; V. V. Bazarny; V. M. Bakhtin; L. G. Polushina; M. A. Kopenkin; D. V. Tolstykh; E. A. Mukhlynina (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2024)
INTRODUCTION. Fluoroquinolones are antibacterial agents associated with adverse drug reactions (ARDs), including aortic lesions; this ARD risk limits the use of fluoroquinolones. Moreover, fluoroquinolones have been reported to induce lesions in other connective tissues (cartilage, tendons), associated with magnesium deficiency.AIM. The study aimed to analyse the effects of magnesium orotate on the thoracic aorta in laboratory rabbits treated with levofloxacin.MATERIALS AND METHODS. The study randomised laboratory rabbits into 3 groups of 10 animals each to receive oral doses of either the carrier solution (control group), or 150 mg/kg/day levofloxacin (levofloxacin group), or 150 mg/ kg/day levofloxacin and 140 mg/kg/day magnesium orotate (levofloxacin/magnesium group). After 14 days of treatment, venous blood samples were taken to determine the serum levels of magnesium, matrix metalloproteinase-9 (MMP-9), and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1), as well as MMP-9 to TIMP-1 ratios. The authors conducted morphological and mechanical characterisation of thoracic aorta samples; the mechanical characterisation involved uniaxial tensile testing. Data are presented as the mean and standard deviation values.RESULTS. The study did not detect any changes in the serum MMP-9, TIMP-1, and magnesium levels or in the MMP-9/TIMP-1 ratios. The authors identified foci of moderate elastic fibre fragmentation in the aortic media in 5 of 10 aortic samples from the levofloxacin group, in 1 of 10 samples from the levofloxacin/magnesium group, and in none from the control group (p=0.013). Rabbits from the levofloxacin group had significantly fewer medial elastic membranes than the others (p=0.015; vs the control group: p=0.022), and their elastic mem